Associations between early thiamine administration and clinical outcomes in critically ill patients with acute kidney injury. Issue 2 (28th July 2022) - Li, Xunliang; Luan, Hong; Zhang, Hui; Li, Chenyu; Bu, Quandong; Zhou, Bin; Tang, Nina; Zhou, Haiyan; Xu, Yan; Jiang, Wei; Zhao, Long; Man, Xiaofei; et al.
Abstract: The effects of early thiamine use on clinical outcomes in critically ill patients with acute kidney injury (AKI) are unclear. The purpose of this study was to investigate the associations between early thiamine administration and clinical outcomes in critically ill patients with AKI. The data of critically ill patients with AKI within 48 h after ICU admission were extracted from the Medical Information Mart for Intensive Care III (MIMIC III) database. PSM was used to match patients early receiving thiamine treatment to those not early receiving thiamine treatment. The association between early thiamine use and in-hospital mortality due to AKI was determined using a logistic regression model. A total of 15 066 AKI patients were eligible for study inclusion. After propensity score matching (PSM), 734 pairs of patients who did and did not receive thiamine treatment in the early stage were established. Early thiamine use was associated with lower in-hospital mortality (OR 0·65; 95 % CI 0·49, 0·87; P < 0·001) and 90-d mortality (OR 0·58; 95 % CI 0·45, 0·74; P < 0·001), and it was also associated with the recovery of renal function (OR 1·26; 95 % CI 1·17, 1·36; P < 0·001). In the subgroup analysis, early thiamine administration was associated with lower in-hospital mortality in patients with stages 1 to 2 AKI. Early thiamine use was associated with improved short-term survival in critically ill patients with AKI. It was possible beneficial role in patients with stages 1 to 2 AKI according to the Kidney Disease: Improving Global Outcomes criteria.